Fundamental Pathogenesis of Atherosclerosis - Maha Ayoub (Challenges and Advances in Pharmaceutical Research Vol. 8, 2022)
Atherosclerosis is characterized by the presence of apolipoprotein B-lipoproteins in the arterial matrix, which serve as an attraction for monocytes that develop into macrophages and dendritic cells. The subendothelial layer thickens because of a maladaptive inflammatory response triggered by macrophages differentiated from recruited monocytes. Myocardial infarction, stroke, and sudden cardiac death can all be caused by lesions. Knowledge of the etiology of atherosclerosis that is rapidly expanding, as well as the development of innovative, target-specific treatments, is altering the cure of atherosclerosis. As a result, a range of therapies are currently being evaluated for their capacity to alleviate the inflammatory pathways likely to trigger and promote the atherosclerotic process. Although the intricate pathophysiology of atherosclerosis remains unknown, recent research has focused on elucidating the disease at the molecular level by studying atherogenesis. Endothelial dysfunction, fatty streak formation, fibrous plaque formation, and plaque rupture are some of the mechanisms that will be studied in this study to better understand how atherosclerosis progresses (Fig. 1). The pathological and molecular mechanisms of atherosclerotic plaque generation and growth are discussed in detail in this article. This review focuses on the specific targets of atherosclerosis and discusses the disease’s pathogenesis and development.